Granulocytic Myeloid-Derived Suppressor Cell Exosomal Prostaglandin E2 Ameliorates Collagen-Induced Arthritis by Enhancing IL-10+ B Cells - Wu, Xinyu; Zhu, Dongwei; Tian, Jie; Tang, Xinyi; Guo, Hongye; Ma, Jie; Xu, Huaxi; Wang, Shengjun (Frontiers in Immunology, 2020)
The results of recent studies have shown that granulocytic-myeloid derived suppressor cells (G-MDSCs) can secrete exosomes that transport various biologically active molecules with regulatory effects on immune cells. However, their roles in autoimmune diseases such as rheumatoid arthritis remain to be further elucidated. In the present study, we investigated the influence of exosomes from G-MDSCs on the humoral immune response in murine collagen-induced arthritis (CIA). G-MDSCs exosomes-treated mice showed lower arthritis index values and decreased inflammatory cell infiltration. Treatment with G-MDSCs exosomes promoted splenic B cells to secrete IL-10 both in vivo and in vitro. In addition, a decrease in the proportion of plasma cells and follicular helper T cells was observed in drainage lymph nodes from G-MDSCs exosomes-treated mice. Moreover, lower serum levels of IgG were detected in G-MDSCs exosomes-treated mice, indicating an alteration of the humoral environment. Mechanistic studies showed that exosomal prostaglandin E2 (PGE2) produced by G-MDSCs upregulated the phosphorylation levels of GSK-3β and CREB, which play a key role in the production of IL-10+B cells. Taken together, our findings demonstrated that G-MDSC exosomal PGE2 attenuates CIA in mice by promoting the generation of IL-10+ Breg cells.